Unmasking white fragility: how whiteness and white student resistance impacts anti-racist education. Issue 1 (2nd January 2020) - Evans-Winters, Venus E.; Hines, Dorothy E.
ABSTRACT: The authors analyse how white undergraduate pre-service teachers resist anti-racist teacher education courses, and how acts of white fragility and white student resistance are employed against Black female professors. In this discussion, we draw from our experiences as two Black women faculty at two predominately white institutions (PWI). Using Critical Race Feminism we discuss how white student resistance is manifested in social interactions with Black female faculty, and how the racialized and gendered spaces of higher education, specifically teacher education, impacts teaching and learning. We introduce a conceptual framework for elucidating white student resistance using psychological and sociological concepts including 1) passive-aggressive behaviours, 2) groupthink, 3) lynch mob, and 4) bystander's effect. This article advances scholarship on white student resistance to non-hegemonic curriculum in higher education, and how whiteness structures student's ability to develop anti-racist praxis.